Pharmaceutical Potential of 2’,4’-Dichloro-4-Hydroxy-3-Methoxychalcone Synthesized from Vaniline - Eka Rizky Meilinda; Hajrah Hajrah; Agung Rahmadani; Laode Rijai (Journal of Tropical Pharmacy and Chemistry, 2018)
Chalcone is an intermediate compound as the main precursor for the biosynthesis of flavonoid in plants. Chalcone has been known to have variety of different pharmacological activities. The difference in chalcone activity is influenced by the differences of subtituents found in both aromatic rings on the chalcone stucture. This study performed the synthesis of 2',4'-dichloro-4-hydroxy-3-methoxychalcone compound from the raw material of 2,4-dichloro acetophenone and vanillin by Claisen-Schmidt reaction using conventional method by stirring. The yield of synthesized compound is 91.57% of purity. The synthesized compounds were characterized by structural elucidation methods using IR, MS, 1H-NMR and 13C-NMR. Toxicity and antioxidant activity tests were performed on the synthesized compound. Base on the test results obtained LC50 value of 20.04 ppm and IC50 26.10 ppm. It is better to describe the pharmaceutical potential of 2',4'-dichloro-4-hydroxy-3-methoxychalcone little bit further.